Identification and trajectory of multimorbidity patterns among older people in China: a longitudinal study based on the China health and retirement longitudinal study 2011–2020 data - Liu, Qian; Lin, Shuzhi; Yin, Lin; Liu, Wei; Zhu, Xiaoying; Li, Zimeng; Shen, Yifang; Feng, Bianling (Frontiers in Public Health, 2025)
BackgroundMultimorbidity presents a significant global health challenge, particularly among older people in China; however, research on its patterns and dynamic evolution remains limited. This study examines chronic disease co-occurrence and associated risk factors, identifying multimorbidity trends to inform health management and policy.MethodsThis study utilized the latest five-wave national survey data from the China Health and Retirement Longitudinal Study (CHARLS) on 2,798 individuals aged 60 years or older with multimorbidity. Latent class analysis (LCA) identified distinct multimorbidity patterns from 14 self-reported chronic conditions. Longitudinal follow-up data were then used to construct transition frequency matrices, modeling the trajectory and dynamic evolution of multimorbidity among older people in China over time.ResultsUsing LCA, 2,798 participants were classified into four patterns: the multi-system disorder group (10.33%), the gastrointestinal metabolism group (44.07%), the cardiovascular disease group (37.81%), and the respiratory disease group (7.79%). Over five waves, the gastrointestinal metabolism group declined (from 74.70% in 2011 to 44.07% in 2020), while the cardiovascular group increased (from 15.87 to 37.81%). The multi-system and respiratory groups also grew. Transition analysis showed the gastrointestinal metabolism group was the least stable, with many shifting to the cardiovascular group (7.29% from 2013 to 2015, 23.81% from 2015 to 2018, 18.54% from 2018 to 2020).ConclusionThe disease burden among older people is shifting from gastrointestinal metabolism disorders to cardiovascular diseases, with gastrointestinal issues potentially acting as precursors to cardiovascular conditions. Future research should investigate the risk factors influencing transitions between multimorbidity patterns and their underlying mechanisms.